HIV case finding among tuberculosis patients at primary health centers in Garut District, West Java - Luthva Luviandani Pratiwi (BKM Public Health and Community Medicine, 2021)
Background: Indonesia is the country with the third-highest tuberculosis case in the world according to WHO in 2018, in addition to having a high TB ​​burden, it also has a TB-HIV burden. One of the efforts made to control TB-HIV is by conducting HIV counseling and tests (HCT) among TB patients. There has been an increase in the number of TB cases and HIV positive TB cases reported in Garut District, but TB cases documented by HIV testing in 2019 are still very small, namely, 666 (18.92%) cases, allowing for other TB patients whose HIV status is unknown. Purpose: To find out the implementation and barriers of HIV counseling and tests from provider and TB patient's perspectives at Primary Health Centers in Garut District. Method: This type of qualitative research uses a descriptive case study approach with multiple holistic designs. The study was conducted at the Department of Health and 6 primary health centers (with high, moderate, and low HIV test coverage) in Garut District. The research instrument used interview guidelines and sheets checklist. The data collection was carried out by in-depth interviews with 18 informants, and documentation. Data Analysis are using thematic analysis. Results: There are health workers that have not carried out HIV tests in accordance with the guidelines. Barriers to HIV testing from the health workers perspective such as communication difficulties, lack of training, reluctance to offer tests, the burden to offer tests, offer HIV testing to pediatric patients, workload, lack of supervision, lack of motivation, lack of coordination, and the patient is fear and does not feel HIV. Meanwhile, from the patient's perspective, the barriers found were not feeling at risk of HIV, the perception that it was not important to do the test, the fear of knowing the test results, poor knowledge, and the presence of stigma. Conclusion: There is one puskesmas with low coverage that does not routinely offer HIV testing because it is only seen based on the presence or absence of HIV risk. Officers who routinely carry out HIV tests but are inadequate due to a lack of coordination and communication between officers at the primary health centers. There is no TB-HIV training, and a lack of supervision for TB-HIV monitoring and evaluation, so that it requires more support and attention from TB/HIV program officers from the Garut District Health Office to improve the implementation of HCT.